Atomic Stress State Inside fcc and bcc Random Alloys: A First-Principles Approach - Shiihara, Yoshinori; Itai, Yuki; Lobzenko, Ivan; Tsuru, Tomohito (Frontiers in Materials, 2022)
The stress state at an atomic level and its governing physics inside a random alloy are essential elements in developing a model for solid solution strengthening in random alloys, which is one of the primary strengthening mechanisms of high-entropy alloys (HEAs). Through first-principles calculation, we investigated the atomic stress in fcc and bcc random alloys that were subsets of CrMnFeCoNi and VNbMoTW HEAs, respectively. The results showed a correlation between the atomic pressure dispersion and the experimental yield stress for the bcc random alloys, as observed in a previous study on fcc alloys. By focusing on the charge transfer and volume change with respect to a bulk crystal, we examined whether the internal stress fields in the fcc and bcc alloys could be interpreted from a unified viewpoint in terms of these physical quantities. Regression analyses using the random forest method revealed that the charge transfer and volume change simultaneously govern the stress state inside an alloy, albeit with varying degrees of intensity.